PENGARUH COUNTRY OF ORIGIN DAN BRAND AMBASSADOR IDOL KOREATERHADAP MINAT BELI SMARTPHONE SAMSUNG(Studi pada Mahasiswa D-IV Manajemen Pemasaran Tingkat 1-4 Politeknik Negeri Malang) - Rofif Yasykur Fadhlullah; Mohammad Maskan (CV. ADIBA AISHA AMIRA, 2024)
Technological development triggers the changing of human lifestyle. Everything can be done easily through smartphones. Mobile phones do not only function as a communication tool, but also as an auxiliary tool to facilitate human work, such as making documents, designing, and others. Samsung is one of the smartphone brands that offers products to facilitate human work. There are many factors that influence consumers to choose a smartphone among some brands, one of which is the country of origin and the use of brand ambassadors. This study aimed to examine the effect of country of origin and brand ambassadors partially and simultaneously on purchase intention. This research is quantitative research with variables country of origin (X1), brand ambassador (X2), and purchase intention (Y). This study used a questionnaire data collection method to 95 respondents who were students of Marketing Management Study Program of Business Department, State Polytechnic of Malang, who were obtained with a simple random sampling technique. The data analysis technique in this study was multiple linear regression analysis. The results of partial hypothesis testing showed that country of origin has a positive effect on buying interest, and brand ambassadors have a positive effect on buying interest. The test results simultaneously showed that country of origin and brand ambassadors positively influence purchase intentions. In the coefficient of determination test, it showed that the influence of country of origin and brand ambassadors on purchase intention was 21.4%, and the remaining 78.7% was influenced by other variables that were not studied in this study. Based on the results of this study, it can be concluded that the country of origin and brand ambassador influence the purchase intention of Samsung smartphones in the D-IV student's environment of the State Polytechnic of Malang. Samsung needs to maintain and continuously improve product design, choose the next brand ambassador with good intelligence, and strengthen their brand compared to other brands